Diffusion Spectrum Imaging of Corticospinal Tracts in Idiopathic Normal Pressure Hydrocephalus - Zhang, Hong; He, Wen-Jie; Liang, Li-Hong; Zhang, Han-Wen; Zhang, Xie-Jun; Zeng, Liang; Luo, Si-Ping; Lin, Fan; Lei, Yi (Frontiers in Neurology, 2021)
Purpose: The purpose of this study was to measure the diffusion spectrum imaging (DSI) parameters of corticospinal tracts (CSTs) and evaluate diffusional changes in CSTs in patients with idiopathic normal pressure hydrocephalus (iNPH) by DSI. Methods: Twenty-three iNPH patients and twenty-one healthy controls (HCs) were involved in this study. Brain DSI data for all participants were collected through the same MR scanning procedure. The diffusion parameters measured and analyzed included quantitative anisotropy (QA), the isotropic diffusion component (ISO), general fractional anisotropy (GFA), fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) of corticospinal tracts. Results: The QA and ISO values of corticospinal tracts in iNPH patients were significantly lower than those in HCs (PLQA = 0.008, PRQA = 0.016, PLISO = 0.024, PRISO = 0.016). The mean MD, AD, and RD values in iNPH patients were significantly higher than those in HCs (PMD = 0.032, PAD = 0.032, PRD = 0.048,). No significant differences in GFA and FA values were noted between iNPH patients and HCs. Conclusion: Decreased QA and ISO values of corticospinal tracts were found in iNPH patients. Quantitative CST evaluation using DSI may lead to information that can improve the present understanding of the disease mechanism.